SHARIA BANK READINESS IN FACING THE GLOBAL RECESSION: KESIAPAN BANK SYARIAH DALAM MENGHADAPI RESESI GLOBAL - Gentri Waruwu; Sepma Wati Dakhi (UPMI Proceeding Series, 2023)
The level of awareness of archives among the public, especially in government and private institutions and agencies, is one illustration that up to now archives have been considered less important. Where archives are records of activities or events in various forms and media in accordance with developments in information and communication technology created and accepted by state institutions, regional governments, educational institutions, companies, political organizations, community organizations and individuals in the implementation of social, national and social life. patriotic. (UU43/2009, article 1 number 2).In the program process, activities are carried out from the initial steps to socialization and introduction regarding awareness about archives to implementation and the final step, namely evaluation. These steps can help achieve goals, increasing awareness of the importance of archives for all employees and helping archive management in the Lolomoyo village environment, South Nias Regency.